Cold storage-induced protein denaturation and functional deterioration of freeze-dried surimi powder - Jong Bong Lee; Hyeong Jun Kim; Yihui Fan; Na Young Yoon; Jun Hee An; Min Jae Kim; Ha Eun Park; Ga Yeon Kwon; Kanako Hashimoto; Kil Bo Shim (Food Chemistry, 2026)

Development of 5-year risk prediction models for incident dementia and mortality in a community-dwelling older Japanese population: The Japan Prospective Studies Collaboration for Aging and Dementia (JPSC‐AD) - Xiangyin Meng; Takanori Honda; Tomoyuki Ohara; Yoshihiko Furuta; Mao Shibata; Jun Hata; Yasuyuki Taki; Tatsuya Mikami; Tetsuya Maeda; Kenjiro Ono; Masaru Mimura; Ritsuko Hanajima; et al. (GeroScience, 2026)
Improving cognitively healthy survival is important for achieving healthy aging. Therefore, it would be valuable to estimate the future risk of either incident dementia or death in community-dwelling older adults. This study aimed to develop a set of risk prediction models for either incident dementia or death that can be applied according to data availability across diverse clinical settings, using longitudinal data from community-dwelling older Japanese adults. A total of 8,334 participants aged ≥65 years were prospectively followed up from 2016 to 2023. Logistic regression was used to develop multivariable prediction models. The developed models were translated into simplified scoring systems based on the β coefficients. The discrimination abilities of the models were assessed by C-statistics, and the calibration was assessed by calibration plots. During the follow-up period, 1,151 participants developed either dementia or death. In the multivariable model using potential predictors commonly available in the primary care setting, age, male sex, formal education ≤9 years, diabetes mellitus, use of lipid-lowering agents, leanness, history of stroke, history of heart disease, history of respiratory disease, history of cancer, current smoking, no regular exercise habit, and low frequency of social interactions were selected as predictors. Adding cognitive status, depressive symptoms, apolipoprotein E-ε4 carrier status, and brain MRI markers to the model further enhanced its predictive performance. The developed models and simplified scores showed good discrimination and calibration. Risk stratification with our models may be useful for assessing the risks of incident dementia and death and, consequently, for prolonging cognitively healthy survival.

From the plate to the brain: associations between dietary patterns and reduced dementia prevalence and white matter lesions in older Japanese adults - Liying Chen; Yasuko Tatewaki; Benjamin Thyreau; Kazuhiro Uchida; Hikari Iki; Shigeyuki Nakaji; Tetsuya Maeda; Kenjiro Ono; Moeko Noguchi-Shinohara; Masaru Mimura; Kenji Nakashima; Jun-ichi Iga; et al. (GeroScience, 2025)
Diet is widely considered essential in dementia, but its association with white matter lesions (WMLs) remains unclear. This cross-sectional study investigated the associations between dietary patterns, dementia, and WMLs in a large, nationwide, multicenter population of older Japanese adults. A total of 8,938 adults (aged ≥ 65; 73 ± 6.3 years old) from the Japan Prospective Studies Collaboration for Aging and Dementia (JPSC-AD) were included. Dietary intake was assessed using a Food Frequency Questionnaire. Principal component analysis was used to derive dietary patterns. A trained Convolutional Neural Network model segmented WMLs from brain MR images. Logistic regression estimated odds ratios (ORs) for dementia by dietary pattern quartiles, while linear regression assessed associations with WML volumes. Five dietary patterns were extracted. A Japanese diet including protein and minerals was significantly associated with lower prevalence of all-cause dementia (OR = 0.56) and Alzheimer’s disease (OR = 0.47), and with reduced WML volume ( β = − 0.03). Similar directional trends in ORs were observed across study sites. The reverse association with WMLs remained significant among individuals without dementia, reducing the likelihood of reverse causation. A Japanese diet including protein and minerals was associated with lower dementia prevalence and smaller WML volume in older Japanese adults. Drawing on nationwide, large-scale, multicenter data, these findings advance our understanding of dietary patterns in older Japanese adults and provide valuable insights for future intervention studies targeting diet and age-related brain changes.

Correction: Progressive multifocal leukoencephalopathy during 4 years of Palbociclib for advanced breast cancer with a history of follicular lymphoma patient - Mariko Nishihara; Ryosuke Koyamada; Tetsuhiro Masaki; Tomohito Shimada; Kazuhiro Ishikawa; Jun Hashimoto; Nobuyoshi Mori; Asami Namai; Hideaki Yokoo; Kenta Takahashi; Tadaki Suzuki; Kazuo Nakamichi; et al. (Journal of NeuroVirology, 2025)

Progressive multifocal leukoencephalopathy during 4 years of Palbociclib for advanced breast cancer with a history of follicular lymphoma patient - Ryosuke Koyamada; Mariko Nishihara; Tetsuhiro Masaki; Tomohito Shimada; Kazuhiro Ishikawa; Jun Hashimoto; Nobuyoshi Mori; Asami Namai; Hideaki Yokoo; Kenta Takahashi; Tadaki Suzuki; Kazuo Nakamichi; et al. (Journal of NeuroVirology, 2025)
A 67-year-old woman with a history of follicular lymphoma and recurrent breast cancer with multiple metastasis developed PML during receiving fluvestrant plus palbociclib. Rituximab and bendamustine had finished 6.5 years ago. Discontinuing palbociclib and using mirtazapine, she is alive a year after diagnosis of PML. It is rare for PML to be diagnosed long after the last dose of rituximab and bendamustine. We will discuss the possible involvement of palbociclib in the course of PML.

Induction of osteogenic differentiation by the extracellular matrix of fetal bone tissues and adult cartilage - Jun Negishi; Dan Tanaka; Yoshihide Hashimoto (Tissue and Cell, 2024)

Degranulation and expression of cytokines were modulated by diazinon in activated mast cells - Tomoko Ohdachi; Miyoko Matsushima; Moeko Ohara; Hina Kawashima; Goki Inoue; Kazuko Atsumi; Yuka Tsubosaki; Masahiro Takekoshi; Jun Ueyama; Naozumi Hashimoto; Mitsuo Sato; Yoshinori Hasegawa; et al. (Toxicology, 2024)

Impact of Habitual Yogurt Intake in Mother–Child Dyads on Incidence of Childhood Otitis Media: The Japan Environment and Children’s Study (JECS) - Masahiro Tsuchiya; Shinobu Tsuchiya; Haruki Momma; Ryoukichi Ikeda; Jun Suzuki; Ryoichi Nagatomi; Nobuo Yaegashi; Takahiro Arima; Kaoru Igarashi; Michihiro Kamijima; Shin Yamazaki; Yukihiro Ohya; et al. (Probiotics and Antimicrobial Proteins, 2024)

Evolution of droplet size of Jet-A surrogate fuel measured by High-Speed interferometric laser imaging for droplet sizing in high temperature region formed by Methane/Air flat flame in laminar counterflow field - Jun Hayashi; Nozomu Hashimoto; Yoshiaki Okubo; Noriaki Nakatsuka; Yasue Tanaka; Tomohiro Hori; Fumiteru Akamatsu (Fuel, 2023)

Effects of ABCB1 and ABCG2 polymorphisms on the pharmacokinetics of abemaciclib - Akimitsu Maeda; Hitoshi Ando; Kei Irie; Naoya Hashimoto; Jun-ichi Morishige; Shoji Fukushima; Akira Okada; Hiromichi Ebi; Masahide Matsuzaki; Hiroji Iwata; Masataka Sawaki (European Journal of Clinical Pharmacology, 2022)

Correction to: Assessment of Polygala paniculata (Polygalaceae) characteristics for evolutionary studies of legume–rhizobia symbiosis - Yuji Tokumoto; Kayo Hashimoto; Takashi Soyano; Seishiro Aoki; Wataru Iwasaki; Mai Fukuhara; Tomomi Nakagawa; Kazuhiko Saeki; Jun Yokoyama; Hironori Fujita; Masayoshi Kawaguchi (Journal of Plant Research, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s10265-021-01295-3

Risk factors for 30-day mortality among patients with Stenotrophomonas maltophilia bacteraemia - Takehiro Hashimoto; Kosaku Komiya; Naoko Fujita; Yuko Usagawa; Mari Yamasue; Kenji Umeki; Masaru Ando; Shin-ichi Nureki; Kazufumi Hiramatsu; Jun-ichi Kadota (Infectious Diseases, 2020)

Assessment of Polygala paniculata (Polygalaceae) characteristics for evolutionary studies of legume–rhizobia symbiosis - Yuji Tokumoto; Kayo Hashimoto; Takashi Soyano; Seishiro Aoki; Wataru Iwasaki; Mai Fukuhara; Tomomi Nakagawa; Kazuhiko Saeki; Jun Yokoyama; Hironori Fujita; Masayoshi Kawaguchi (Journal of Plant Research, 2020)
Root nodule (RN) symbiosis is a mutualistic interaction observed between nitrogen-fixing soil bacteria and nodulating plants, which are scattered in only four orders of angiosperms called nitrogen-fixing clade. Most of legumes engage in RN symbiosis with rhizobia. Molecular genetic analyses with legumes and non-leguminous nodulating plants revealed that RN symbiosis utilizes early signalling components that are required for symbiosis with arbuscular mycorrhizal (AM) fungi. However detailed evolutionary processes are still largely unknown. Comparative analyses with non-nodulating species phylogenetically related to legumes could be better strategies to study the evolution of RN symbiosis in legumes. Polygala paniculata is a non-leguminous species that belongs to a family different from legumes but that is classified into the same order, Fabales. It has appropriate characteristics for cultivation in laboratories: small body size, high fertility and short lifecycles. Therefore, we further assessed whether this species is suitable as a model species for comparative studies with legumes. We first validated that the plant we obtained in Palau was truly P. paniculata by molecular phylogenetic analysis using rbc L sequences. The estimated genome size of this species was less than those of two model legumes, Lotus japonicus and Medicago truncatula . We determined conditions for cultivation in vitro and for hairy root formation from P. paniculata seedlings. It would facilitate to investigate gene functions in this species. The ability of P. paniculata to interact with AM fungi was confirmed by inoculation with Rhizophagus irregularis , suggesting the presence of early signalling factors that might be involved in RN symbiosis. Unexpectedly, branching of root hairs was observed when inoculated with Mesorhizobium loti broad host range strain NZP2037, indicating that P. paniculata has the biological potential to respond to rhizobia. We propose that P. paniculata is used as a model plant for the evolutionary study of RN symbiosis.

Origin of the early Cenozoic belt boundary thrust and Izanagi–Pacific ridge subduction in the western Pacific margin - Gaku Kimura; Yujin Kitamura; Asuka Yamaguchi; Jun Kameda; Yoshitaka Hashimoto; Mari Hamahashi (Island Arc, 2019)
The belt boundary thrust within the Cretaceous–Neogene accretionary complex of the Shimanto Belt, southwestern Japan, extends for more than ~ 1 000 km along the Japanese islands. A common understanding of the origin of the thrust is that it is an out of sequence thrust as a result of continuous accretion since the late Cretaceous and there is a kinematic reason for its maintaining a critically tapered wedge. The timing of the accretion gap and thrusting, however, coincides with the collision of the Paleocene–early Eocene Izanagi–Pacific spreading ridges with the trench along the western Pacific margin, which has been recently re‐hypothesized as younger than the previous assumption with respect to the Kula‐Pacific ridge subduction during the late Cretaceous. The ridge subduction hypothesis provides a consistent explanation for the cessation of magmatic activity along the continental margin and the presence of an unconformity in the forearc basin. This is not only the case in southwestern Japan, but also along the more northern Asian margin in Hokkaido, Sakhalin, and Sikhote‐Alin. This Paleocene–early Eocene ridge subduction hypothesis is also consistent with recently acquired tomographic images beneath the Asian continent. The timing of the Izanagi–Pacific ridge subduction along the western Pacific margin allows for a revision of the classic hypothesis of a great reorganization of the Pacific Plate motion between ~ 47 Ma and 42 Ma, illustrated by the bend in the Hawaii–Emperor chain, because of the change in subduction torque balance and the Oligocene–Miocene back arc spreading after the ridge subduction in the western Pacific margin.

EcoBalance 2018—Nexus of ideas: innovation by linking through life cycle thinking (9–12 October 2018, Tokyo, Japan) - Shinsuke Murakami; Jun Nakatani; Kenichi Nakajima; Eri Amasawa; Ryota Ii; Kiyotada Hayashi; Naoki Yoshikawa; Ichiro Daigo; Yusuke Kishita; Tomohiko Ihara; Koichi Shobatake; Yuki Kudoh; et al. (The International Journal of Life Cycle Assessment, 2019)

Lack of deuterium isotope effects in the antidepressant effects of (R)-ketamine in a chronic social defeat stress model - Kai Zhang; Hidetoh Toki; Yuko Fujita; Min Ma; Lijia Chang; Youge Qu; Shingo Harada; Tetsuhiro Nemoto; Akiko Mizuno-Yasuhira; Jun-ichi Yamaguchi; Shigeyuki Chaki; Kenji Hashimoto (Psychopharmacology, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Acoustic properties of deformed rocks in the N obeoka thrust, in the S himanto B elt, K yushu, S outhwest J apan - Yoshitaka Hashimoto; Shogo Abe; Hiroki Tano; Mari Hamahashi; Saneatsu Saito; Gaku Kimura; Asuka Yamaguchi; Rina Fukuchi; Jun Kameda; Yohei Hamada; Yujin Kitamura; Koichiro Fujimoto; et al. (Island Arc, 2017)
Laboratory measurements for compressional and shear wave velocities ( V p and V s, respectively) and porosity were conducted with core samples from the N obeoka T hrust D rilling P roject ( NOBELL ) under controlled effective pressure (5–65 MPa at 5 MPa intervals) and wet conditions. Samples were classified according to deformation texture as phyllite, foliated cataclasite, or non‐foliated cataclasite. Measured values of V p, V s, and porosity are within a range of 5.17–5.57 km/s, 2.60–2.71 km/s, and 2.75–3.10 %, respectively, for phyllite; 4.89–5.23 km/s, 2.46–2.57 km/s, and 3.58–4.53 %, respectively, for foliated cataclasite; and 4.90–5.32 km/s, 2.51–2.63 km/s, and 3.79–4.60 %, respectively, for non‐foliated cataclasite, which are all consistent with the previous laboratory experiments conducted with outcrop samples under dry conditions. However, our results also indicate higher V p and V s and lower porosity than those measured by the previous studies that adopted the wire‐line logging methods. The variations in V p, V s, and porosity are controlled by deformation structure and are greater for phyllite and foliated cataclasite than for non‐foliated cataclasite.

Temporal stress variations along a seismogenic megasplay fault in the subduction zone: A n example from the N obeoka T hrust, southwestern J apan - Ryoji Kawasaki; Mari Hamahashi; Yoshitaka Hashimoto; Makoto Otsubo; Asuka Yamaguchi; Yujin Kitamura; Jun Kameda; Yohei Hamada; Rina Fukuchi; Gaku Kimura (Island Arc, 2017)
The N obeoka T hrust, an ancient megasplay fault in the S himanto B elt, southwestern J apan, contains fault rocks from the seismogenic zone, providing an accessible analog of active megasplay faults in deep subduction settings. In this study, the paleostress along the N obeoka T hrust was analyzed using multiple inversion techniques, including k ‐means clustering of fault datasets acquired from drillcores that intersected the thrust. The six resultant stress orientation clusters can be divided into two general groups: stress solutions with north–south‐trending σ 1 axes, and those with east–west‐trending σ 1 axes. These groups are characterized by the temporal changes for the orientations of the σ 1 and σ 3 principal stress axes that involve alternation between horizontal and vertical. The findings are probably due to a change in stress state before and after earthquakes that occurred on the fault; similar changes have been observed in active tectonic settings, such as the 2011 T ohoku‐ O ki earthquake ( J apan).

Weight under Steel Wheels: Material Stock and Flow Analysis of High‐Speed Rail in China - Tao Wang; Jun Zhou; Ye Yue; Jie Yang; Seiji Hashimoto (Journal of Industrial Ecology, 2016)
Summary The construction of a nation‐wide high‐speed rail (HSR) network has emerged as a hugely expensive and ambitious infrastructure project in China. As of December 2012, some 8,800 kilometers (km) of double‐track HSR lines came into service in the country, accounting for 40% of the total HSR length in the world. The network is expected to expand to 34,000 km or longer in around two decades. As the first HSR system specially built and operated in an economically developing country, it helps integrate the sprawling economy and lift the quality of life of the increasing urban population. China's experiences in HSR are expected to be of value to other countries aiming to adopt bullet train systems, especially those at a similar level of industrialization and urbanization. This work specifically examines material stocks and flows associated with the HSR infrastructure construction in China. A major distinction from the construction of HSR tracks in Europe is that nearly 70% of the HSR tracks in China are laid upon bridges or inside tunnels, which are structures that demand great amounts of raw materials. The entire network, once completed by 2030, will cumulatively require 83 to 137 million tonnes (Mt) of steel and 560 to 920 Mt of cement. This is still a small share of China's use of material resources. Nonetheless, the massive application of the steel‐ and cement‐intensive structures deserves consideration when assessing the environmental performance of HSR over its entire life cycle.

Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Is Involved in Adult Mouse Hippocampal Neurogenesis After Stroke - Minako Matsumoto; Tomoya Nakamachi; Jun Watanabe; Koichi Sugiyama; Hirokazu Ohtaki; Norimitsu Murai; Shun Sasaki; Zhifang Xu; Hitoshi Hashimoto; Tamotsu Seki; Akira Miyazaki; Seiji Shioda (Journal of Molecular Neuroscience, 2016)

Regulation of glutamate transporter 1 via BDNF-TrkB signaling plays a role in the anti-apoptotic and antidepressant effects of ketamine in chronic unpredictable stress model of depression - Wen-Xue Liu; Jing Wang; Ze-Min Xie; Ning Xu; Guang-Fen Zhang; Min Jia; Zhi-Qiang Zhou; Kenji Hashimoto; Jian-Jun Yang (Psychopharmacology, 2016)

No genetic deviation between two morphotypes of the snipefishes (Macroramphosidae: Macroramphosus) in Japanese waters - Taisuke Noguchi; Kay Sakuma; Tomo Kitahashi; Hajime Itoh; Yasunori Kano; Gento Shinohara; Jun Hashimoto; Shigeaki Kojima (Ichthyological Research, 2015)

Genetic population structure of Hemigrammocypris rasborella (Cyprinidae) inferred from mtDNA sequences - Katsutoshi Watanabe; Seiichi Mori; Tetsuo Tanaka; Naoyuki Kanagawa; Takahiko Itai; Jyun-ichi Kitamura; Noriyasu Suzuki; Koji Tominaga; Ryo Kakioka; Ryoichi Tabata; Tsukasa Abe; Yushu Tashiro; et al. (Ichthyological Research, 2014)

New buoy observation system for tsunami and crustal deformation - Narumi Takahashi; Yasuhisa Ishihara; Hiroshi Ochi; Tatsuya Fukuda; Jun’ichiro Tahara; Yosaku Maeda; Motoyuki Kido; Yusaku Ohta; Katsuhiko Mutoh; Gosei Hashimoto; Satoshi Kogure; Yoshiyuki Kaneda (Marine Geophysical Research, 2014)

Description of a new species of the genus Trichopeltarion A. Milne-Edwards, 1880 (Decapoda: Brachyura: Trichopeltariidae) from western Pacific and southeast Asian waters - Tohru Naruse; Jun Hashimoto (Marine Biology Research, 2014)

First report of fig mosaic virus infecting common fig (Ficus carica) in Japan - Kazuya Ishikawa; Kensaku Maejima; Susumu Nagashima; Nobuo Sawamura; Yusuke Takinami; Ken Komatsu; Masayoshi Hashimoto; Yasuyuki Yamaji; Jun Yamamoto; Shigetou Namba (Journal of General Plant Pathology, 2012)

Impact of medium volume and oxygen concentration in the incubator on pericellular oxygen concentration and differentiation of murine chondrogenic cell culture - Hiroki Oze; Makoto Hirao; Kosuke Ebina; Kenrin Shi; Yoshitaka Kawato; Shoichi Kaneshiro; Hideki Yoshikawa; Jun Hashimoto (In Vitro Cellular & Developmental Biology - Animal, 2012)

A precise bathymetric map of the world’s deepest seafloor, Challenger Deep in the Mariana Trench - Masao Nakanishi; Jun Hashimoto (Marine Geophysical Research, 2011)

Harem structure and female territoriality in the dwarf hawkfish Cirrhitichthys falco (Cirrhitidae) - Tatsuru Kadota; Jun Osato; Hiroaki Hashimoto; Yoichi Sakai (Environmental Biology of Fishes, 2011)

Isolation of a Leptothrix Strain, OUMS1, from Ocherous Deposits in Groundwater - Michinori Sawayama; Tomoko Suzuki; Hideki Hashimoto; Tomonari Kasai; Mitsuaki Furutani; Naoyuki Miyata; Hitoshi Kunoh; Jun Takada (Current Microbiology, 2011)

First capture of post-spawning female of the Japanese eel Anguilla japonica at the southern West Mariana Ridge - Hiroaki Kurogi; Makoto Okazaki; Noritaka Mochioka; Tadao Jinbo; Hiroshi Hashimoto; Masanori Takahashi; Atsushi Tawa; Jun Aoyama; Akira Shinoda; Katsumi Tsukamoto; Hideki Tanaka; Koichiro Gen; et al. (Fisheries Science, 2011)

Association Study Between the Pericentrin (PCNT) Gene and Schizophrenia - Shusuke Numata; Masahito Nakataki; Jun-ichi Iga; Toshihito Tanahashi; Yoshihiro Nakadoi; Kazutaka Ohi; Ryota Hashimoto; Masatoshi Takeda; Mitsuo Itakura; Shu-ichi Ueno; Tetsuro Ohmori (NeuroMolecular Medicine, 2010)

Evolutionary relationships of deep-sea mussels inferred by mitochondrial DNA sequences - Hiromi Iwasaki; Akiko Kyuno; Mifue Shintaku; Yuko Fujita; Yoshihiro Fujiwara; Katsunori Fujikura; Jun Hashimoto; Leonardo de Oliveira Martins; Andrey Gebruk; Jun-Ichi Miyazaki (Marine Biology, 2006)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Comprehensive search for chicken W chromosome-linked genes expressed in early female embryos from the female-minus-male subtracted cDNA macroarray - Daisuke Yamada; Yoshiyuki Koyama; Mai Komatsubara; Mayuko Urabe; Masako Mori; Yoichi Hashimoto; Ryosuke Nii; Midori Kobayashi; Ayako Nakamoto; Jun Ogihara; Jun Kato; Shigeki Mizuno (Chromosome Research, 2004)

Hepatocyte growth factor promotes migration of human hepatocellular carcinoma via phosphatidylinositol 3-kinase - Katsuya Nakanishi; Jiro Fujimoto; Takahiro Ueki; Keigo Kishimoto; Tomoko Hashimoto-Tamaoki; Jun-ichi Furuyama; Toshifumi Itoh; Yutaka Sasaki; Eizo Okamoto (Clinical & Experimental Metastasis, 1999)

Development of Anti-Influenza Virus Drugs I: Improvement of Oral Absorption and In Vivo Anti-Influenza Activity of Stachyflin and Its Derivatives - Shigenori Yagi; Junko Ono; Jun Yoshimoto; Ken-ichi Sugita; Naohiko Hattori; Toshihiro Fujioka; Tamio Fujiwara; Hirohiko Sugimoto; Koichiro Hirano; Naofumi Hashimoto (Pharmaceutical Research, 1999)

A novel cytokine-inducing glycolipid isolated from the lipoteichoic acid fraction of Enterococcus hirae ATCC 9790: A fundamental structure of the hydrophilic part - Masahito Hashimoto; Yoshimasa Imamura; Jun-ichi Yasuoka; Shozo Kotani; Shoichi Kusumoto; Yasuo Suda (Glycoconjugate Journal, 1999)

Short Communication: Ames assay with Salmonella typhimurium TA102 for mutagenicity and antimutagenicity of metallic oxide powders having antibacterial activities - Jun Sawai; Hiromitsu Kojima; Fumio Kano; Hideo Igarashi; Atsushi Hashimoto; Emiko Kawada; Takao Kokugan; Masaru Shimizu (World Journal of Microbiology and Biotechnology, 1998)

Characterization of a cry2A Gene Cloned from an Isolate of Bacillus thuringiensis serovar sotto - Jun Sasaki; Shinichiro Asano; Naoki Hashimoto; Bibiana W. Lay; Sugyo Hastowo; Hisanori Bando; Toshihiko Iizuka (Current Microbiology, 1997)

A simple method for screening assessment of acute toxicity of chemicals - Sumie Yamanaka; Masanori Hashimoto; Masuo Tobe; Kazuo Kobayashi; Jun Sekizawa; Masao Nishimura (Archives of Toxicology, 1990)